Regulation of anti-phage defense mechanisms by using cinnamaldehyde as a quorum sensing inhibitor - Barrio-Pujante, Antonio; Bleriot, Inés; Blasco, Lucía; Fernández-Garcia, Laura; Pacios, Olga; Ortiz-Cartagena, Concha; Cuenca, Felipe Fernández; Oteo-Iglesias, Jesús; Tomás, María (Frontiers in Microbiology, 2024)
Background Multidrug resistant bacteria and the shortage of new antibiotics constitute a serious health problem. This problem has led to increased interest in the use of bacteriophages, which have great potential as antimicrobial agents, but which also have the potential to induce resistance. The objective of the present study was to minimize the development of phage resistance in Klebsiella pneumoniae strains by inhibiting Quorum sensing (QS) and thus demonstrate the role of QS in regulating defence mechanisms. Results Cinnamaldehyde (CAD) was added to K. pneumoniae cultures to inhibit QS and thus demonstrate the role of the signalling system in regulating the anti-phage defence mechanism; the QS inhibitory activity of CAD in K. pneumoniae was confirmed by a reduction in the quantitative expression of the lsrB gene (AI-2 Pathway) and by proteomic analysis. Infection assays showed that the phage was able to infect a previously resistant K. pneumoniae strain in the cultures to which CAD was added. The results were confirmed by proteomic analysis. Thus, anti-phage defence-related proteins from different systems such as cyclic oligonucleotide-based bacterial antiphage signalling (CBASS), Restriction-Modification (R-M) Systems, the clustered regularly interspaced short palindromic repeat-Cas (CRISPR-Cas) System and Bacteriophage Control Infection (BCI) were present in the cultures with phage, but not in the cultures with phage and CAD. When the QS and anti-phage defence systems were inhibited by the combined treatment, proteins related to phage infection and proliferation, such as the tail fibre protein, the cell division protein DamX and outer membrane channel protein TolC, were detected. Conclusions Inhibition of QS reduces phage resistance in K. pneumoniae, resulting in infection of a previously resistant strain by phage, with a significant increase in phage proliferation and a significant reduction in bacterial growth. QS inhibitors could be considered for therapeutic application by including them in phage cocktails or in phage-antibiotic combinations to enhance synergistic effects and reduce the emergence of antimicrobial resistance.